Openness to Vegetarian Diets Among Patients With Chronic Disease: Racial Parity Between Black and White Patients - Jennifer Paul-Quinn; Karol Toledo; Mihir Patel (American Journal of Lifestyle Medicine, 2026)
Many lifestyle medicine and primary care practitioners are actively seeking to leverage the benefits of plant-based diets in preventing and managing chronic diseases among their patients. It is important to understand the key barriers that underlie an individual’s openness to adopting a vegetarian diet in an urban, metropolitan area with a predominately Black population. This study used a cross-sectional survey design to assess barriers and openness to vegetarian diets in three outpatient clinics in the Baltimore area. Barriers surveyed included anticipated stigma, tastiness, financial cost, convenience, familiarity, and perceived healthfulness. 124 responses were included. There was no significant difference in mean openness score by race. The average openness score was 4.17 out of 7 among White participants and 4.03 among Black participants (SD 1.1; difference = 0.14; effect size = 0.13; P = .69). There was no significant difference in any barriers by race. Participants reported moderate openness to adopting a vegetarian diet, with no significant differences by race. These findings challenge any assumptions that patients, particularly Black patients, are less interested in vegetarian diets. Patients with chronic disease, regardless of race, may be receptive to information about vegetarian diets, with specific attention to address barriers.